2011
DOI: 10.1080/19942060.2011.11015368
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Flow Patterns in Rectangular Shallow Reservoirs

Abstract: In this study, the capability of a two-dimensional shallow-water numerical model to simulate the symmetric and asymmetric flows that can take place in rectangular shallow reservoirs with different lateral expansion ratios and dimensionless lengths is investigated. Numerically, the main difficulty is to properly reproduce the transition between symmetric and asymmetric flows. For a large lateral expansion ratio, the use of two protocols of simulation highlighted a high sensitivity of the simulated flow pattern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 22 publications
0
26
1
Order By: Relevance
“…Fig. 4 of Dufresne et al, 2011), this feature is not captured in our simple model set-up. This, however, does not hamper the model's ability to deliver realistic transitions between symmetric and asymmetric flow patterns, as shown in Section 3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 4 of Dufresne et al, 2011), this feature is not captured in our simple model set-up. This, however, does not hamper the model's ability to deliver realistic transitions between symmetric and asymmetric flow patterns, as shown in Section 3.…”
Section: Methodsmentioning
confidence: 99%
“…In connected studies, the same group (Camnasio, Erpicum, Archambeau, Pirotton, & Dewals, 2014;Dewals, Kantoush, Erpicum, Pirotton, & Schleiss, 2008;Dufresne, Dewals, Erpicum, Archambeau, & Pirotton, 2011) as well as others (Kantoush, 2008;Peng, Zhou, & Burrows, 2011;Secher et al, 2014;Zhou, Liu, Shafiai, Peng, & Burrows, 2010) successfully simulated the observed flow patterns using the 2D shallow-water equations on a high resolution grid. For a given reservoir geometry, they showed that the flow pattern consistently evolved to a stable symmetric or asymmetric state in accordance with observations.…”
Section: Introductionmentioning
confidence: 99%
“…The time step is adaptive and computed based on the Courant-Friedrichs-Lewy (CFL) stability criterion, with a CFL number equal to 0.5. It takes values of the order of 10 -3 -10 -2 s. This finite volume model has already proven its validity and efficiency for the analysis of natural and artificial floods (Ernst et al, 2010;Erpicum et al, 2010a;Dewals et al, 2011), as well as numerous other applications including complex turbulent flows (Dewals et al, 2008;Erpicum et al, 2009;Roger et al, 2009;Dufresne et al, 2011).…”
Section: Numerical Modelmentioning
confidence: 99%
“…The Darcy-Weisbach standard formulation was used for the friction modelling (Dufresne et al, 2011) and the bottom roughness was set to k s = 0.1 mm (representative of the polyvinylchloride state during the experiments).…”
Section: Experimental Set-upmentioning
confidence: 99%
“…and the flow modellers have successfully demonstrated that these flow features can be reproduced using an operational numerical model, where only the friction modelling is adjustable (Dewals et al, 2008, Dufresne et al, 2011, Peng et al, 2011, Camnasio et al, 2013, Khan et al, 2013, many questions remain regarding meandering flows.…”
mentioning
confidence: 99%